2021
DOI: 10.1007/s40299-021-00602-9
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Classroom-Based Assessment for Young EFL Learners in the Chinese Context: A Case Study

Abstract: While there is extensive literature on how classroom-based assessment (CBA) can be effectively put into practice, little is known about its implementation in L2 contexts, especially in the young English-as-a-foreignlanguage (EFL) learner context. This study endeavored to investigate teachers' CBA practices and factors that might exert influences on them. A purposive sample of three EFL teachers from two primary schools participated in this case study. Our thematic analysis revealed that the potential of CBA in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…These findings indicate that if teachers are to successfully embrace AfL as an approach to engage students, they should be equipped with sufficient AfL-related knowledge and skills, develop a sound understanding of which type of goal orientation can provide an enduring and strong motivation for students in their learning process, and acknowledge their students' agency and invest trust in their students' abilities to take control of their learning. All these points to the significance of the role of teacher education programs (Zhang and Ben Said, 2014;Zhang, 2016Zhang, , 2021; see Gao and Zhang, 2020;Sun and Zhang, 2021;Yan et al, 2021). We suggest that teacher educators help teachers understand the roles of teachers and students in learning and assessment, provide teachers with clear instructions as to how each specific AfL strategy can be used.…”
Section: Discussionmentioning
confidence: 94%
“…These findings indicate that if teachers are to successfully embrace AfL as an approach to engage students, they should be equipped with sufficient AfL-related knowledge and skills, develop a sound understanding of which type of goal orientation can provide an enduring and strong motivation for students in their learning process, and acknowledge their students' agency and invest trust in their students' abilities to take control of their learning. All these points to the significance of the role of teacher education programs (Zhang and Ben Said, 2014;Zhang, 2016Zhang, , 2021; see Gao and Zhang, 2020;Sun and Zhang, 2021;Yan et al, 2021). We suggest that teacher educators help teachers understand the roles of teachers and students in learning and assessment, provide teachers with clear instructions as to how each specific AfL strategy can be used.…”
Section: Discussionmentioning
confidence: 94%
“…Born and brought up in such an entrenched value, NNES teachers probably believe it is their duty to give feedback targeting a variety of errors. In contrast, western education system gives more importance to students' agency in learning and underplays teachers' role (Rao and Li, 2017 ; Yan et al, 2021 ). NES teachers who were brought up and educated in this culture may support that it is important for students to accept the responsibility to identify their errors by themselves, and so it is unnecessary for teachers to mark errors comprehensively.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, in mainland China, where significant correlations were found between self-assessment of reading/writing scores and reading comprehension/writing test scores, Liu and Brantmeier’s (2019) study has demonstrated that Chinese young learners could self-assess their English reading/writing skills and knowledge quite accurately. Nevertheless, further details are needed not only regarding the processes that young learners use to self-assess their reading and writing, but also how language teachers’ assessment literacy can be further developed to support students’ growing needs in such assessment activities ( Yan et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is a growing recognition of the value for teachers to implement Assessment for Learning (AfL), namely, a student-centered assessment approach, in classrooms globally ( Birenbaum et al, 2015 ; Tai et al, 2018 ; Dixon et al, 2020 ). In the Chinese context, although AfL has been promoted across university classes at the policy level, for example, the Ministry of Education (MoE) of China has proposed and stressed AfL to be prioritized in every major curriculum in classroom practices ( MoE P. R. China, 2017 ), EFL teaching and assessment are still mostly confined to an exam-driven, product-oriented, and teacher-dominated environment, particularly in the writing domain (see Berry, 2011 ; Brown and Gao, 2015 ; Reinders et al, 2017 ; Wu et al, 2021a ; Yan et al, 2021 ). Therefore, how policies are enacted in EFL classroom assessment practices and how teachers conceive student-led assessment approaches are of significance and the latter is part of the current research endeavor.…”
Section: Introductionmentioning
confidence: 99%